Effects of dance sports exercise on vestibular function and balance of children with sensorineural hearing loss; a randomized quasi-experimental trial - Hu, Fang; Qiu, Xuan; Wu, Xinbo; Wu, Xilong; Li, Han; Kim, Sukwon (Frontiers in Pediatrics, 2024)
Background: Sensorineural hearing loss (SNHL) children have difficulty living and limited movement due to impaired vestibular function and reduced balance ability. Objectives: The present study evaluated the effects of Latin dance training on the vestibular function and balance of SNHL children. Methods: Thirty SNHL children with no difference in vestibular function and balance ability were randomly divided into two groups, the Latin dance training group (LTG, n=15) and the control group (CONG, n=15).Vestibular function, timed eyes-closed static (ECS) and functional reach test (FRT) were measured before and after the intervention, and a two-way repeated-measures analysis of variance was performed. Results:After training, the vestibular function performance of LTG was higher than that of CONG (CONG: 16.425